Developing University Students’ Critical Thinking through the Depopulation Phenomenon in Kōfu Town_A Pedagogical Study of Nihonjijō - Putra, Jeni; Widianti, Susi; Hayati, Novia (Fast in Humanities, 2026)
Japan's rural depopulation has emerged as a critical socio demographic issue closely intertwined with population aging and sustained urban migration, and within Nihonjijo education it provides an authentic and socially grounded context for cultivating students' critical engagement with contemporary Japanese society, enabling to move beyond descriptive cultural knowledge toward higher-order thinking. This study investigate how undergraduate students apply Paul and Elder's critical Thinking framework when engaging with the depopulation case of Kofu Town, Tottori, Prefecture. Data comprised thirty Indonesian language essays (approximately 400 -500 words each) produced by students enrolled in a Nihonjijo Course at UNIKOM Bandung. Using qualitative content analysis, essays were classified  into six cognitive stages. Knowledge, comprehension, application, analysis, synthesis, and action. The findings show that students reached the action stage, higher-level responses were characterised by contextual interpretation of datam integration of multiple information sources, and comparative reflection linking Japan's condition with parallel challenges in Indonesia. Overall, the results suggest that Nihonjijo learning can function as a pedagogixal space for developing socio-cultural awareness and reflective reasoning rather than merely transmitting factual content, and the study therefore recommends the explicit embedding of critical thinking frameworks in course design, the use of inquiry-based learning activities, and assesment practices oriented toward analytical and reflective outputs; future research should explore the longitudinal effects of sustained critical thinking instruction across multiple Nihonjijo courses,